Tantangan Demokratisasi: Melindungi Hak Kelompok Lintas Batas di Era Globalisasi (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Globalization has transformed the way nations interact, bringing challenges in protecting the rights of cross-border groups such as migrants, international workers, and minorities. On one hand, globalization promotes closer international cooperation and strengthens the commitment to universal human rights. However, on the other hand, policies implemented by states often fail to align with these changes, creating various obstacles in efforts to protect vulnerable groups caught in different legal systems. This article explores the main challenges faced in protecting the rights of cross-border groups amid the dynamics of globalization. The research employs an in-depth literature review method, focusing on studies related to democratization, human rights, and the challenges encountered by cross-border groups. The findings reveal that, despite significant progress in the international framework on human rights, there remains a gap between policy and practical implementation that affects the protection of cross-border groups. This research also provides policy recommendations to help address these challenges in the era of globalization.